2022
DOI: 10.1111/jjns.12512
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of auricular acupressure on pain management during labor: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Aim: This meta-analysis aimed to systematically evaluate the effectiveness of auricular acupressure on pain management during labor.Methods: Six English and three Chinese electronic databases were comprehensively searched from inception to 6 November 2021. The PRISMA checklist was followed. The methodological quality of the included studies was assessed with the Cochrane Collaboration Bias Risk Assessment Tool. The metaanalysis was performed using Review Manager 5.3 software. Heterogeneity between studies was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…An extensive review analysis found that 92% of 27 studies focusing on auricular acupressure for acute pain showed effectiveness [23] . A meta-analysis of 5 randomized controlled trials also showed that labor pain scores were significantly lower in the auricular massage group than in the usual care group at cervix dilation of 6, 8, and 10 cm [15] . Although this study focused on pregnant women during the incubation, the findings are consistent with previous conclusions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An extensive review analysis found that 92% of 27 studies focusing on auricular acupressure for acute pain showed effectiveness [23] . A meta-analysis of 5 randomized controlled trials also showed that labor pain scores were significantly lower in the auricular massage group than in the usual care group at cervix dilation of 6, 8, and 10 cm [15] . Although this study focused on pregnant women during the incubation, the findings are consistent with previous conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…Severe pain and anxiety during this phase can lead to a range of complications, including prolonged labor, instrumental deliveries, abnormal fetal heart rate patterns, and neonatal hospitalization [12] . Although previous studies have explored the effects of auricular point therapy during the active phase of labor, there is limited research on its efficacy during the latent phase [13][14][15] .…”
mentioning
confidence: 99%